Medication Changes After Renal Denervation: Current Evidence and Patient Perspectives - Zhipeng Zhang; Fei Zhao; Runyu Ye; Xin Zhang; Yong Peng; Xiaoping Chen; Kai Liu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Renal denervation (RDN) is recognized as an adjunct therapy for hypertension management with a favorable and consistent blood pressure–lowering efficacy and safety profile. Alteration in medication burden is another noteworthy outcome of RDN for clinicians and patients. In this review, we summarized current clinical trials and patient perspectives, focusing on the use of antihypertensive medication (AHM) after RDN. The results of randomized controlled trials demonstrated that patients undergoing RDN exhibited lower blood pressure levels with a similar AHM burden or similar blood pressure levels with fewer AHMs than the sham control group. In studies with follow‐ups of ≤6 months, AHM use increased or remained generally consistent in patients undergoing RDN, which may be attributed to the prespecified study process. In studies with follow‐ups of >6 months, the blood pressure–lowering efficacy of RDN was consistent with a decreasing or similar AHM burden compared with baseline conditions, except for the 36‐month results in the SPYRAL HTN‐ON MED (Safety and Efficacy of Renal Denervation in Patients Taking Antihypertensive Medications) trial. Huge gaps exist between current evidence on medication changes after RDN and patient expectations, which may be addressed through adequate communication in a shared decision‐making process and further improvement of the RDN procedure. Moreover, novel evaluation methodologies for assessing medication burden changes, incorporating adherence to AHMs and modifications in drug classes, may be required to evaluate the impact of RDN on medication usage in the future.